Difference between revisions of "009B Sample Midterm 2, Problem 5"

From Math Wiki
Jump to navigation Jump to search
(Replaced content with "<span class="exam"> Evaluate the integral: ::<math>\int \tan^4 x ~dx</math> <hr> '''<u>Solution</u>''' 009B Sample Midt...")
 
(One intermediate revision by the same user not shown)
Line 3: Line 3:
 
::<math>\int \tan^4 x ~dx</math>
 
::<math>\int \tan^4 x ~dx</math>
  
 +
<hr>
 +
[[009B Sample Midterm 2, Problem 5 Solution|'''<u>Solution</u>''']]
  
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
+
[[009B Sample Midterm 2, Problem 5 Detailed Solution|'''<u>Detailed Solution</u>''']]
!Foundations: &nbsp;
 
|-
 
|Recall:
 
|-
 
|'''1.''' <math style="vertical-align: -1px">\sec^2x=\tan^2x+1</math>
 
|-
 
|'''2.''' <math style="vertical-align: -13px">\int \sec^2 x~dx=\tan x+C</math>
 
|-
 
|How would you integrate <math style="vertical-align: -12px">\int \sec^2(x)\tan(x)~dx?</math>
 
|-
 
|
 
::You could use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -2px">u=\tan x.</math> Then, <math style="vertical-align: -5px">du=\sec^2(x)dx.</math> Thus,
 
|-
 
|
 
::<math>\begin{array}{rcl}
 
\displaystyle{\int \sec^2(x)\tan(x)~dx} & = & \displaystyle{\int u~du}\\
 
&&\\
 
& = & \displaystyle{\frac{u^2}{2}+C}\\
 
&&\\
 
& = & \displaystyle{\frac{\tan^2x}{2}+C.}\\
 
\end{array}</math>
 
|}
 
  
  
'''Solution:'''
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|First, we write
 
|-
 
|
 
::<math style="vertical-align: -13px">\int \tan^4(x)~dx=\int \tan^2(x) \tan^2(x)~dx.</math>
 
|-
 
|Using the trig identity <math style="vertical-align: -5px">\sec^2(x)=\tan^2(x)+1,</math> we have
 
|-
 
|
 
::<math style="vertical-align: -5px">\tan^2(x)=\sec^2(x)-1.</math>
 
|-
 
|Plugging in the last identity into one of the <math style="vertical-align: -5px">\tan^2(x),</math> we get
 
|-
 
|
 
::<math>\begin{array}{rcl}
 
\displaystyle{\int \tan^4(x)~dx} & = & \displaystyle{\int \tan^2(x) (\sec^2(x)-1)~dx}\\
 
&&\\
 
& = & \displaystyle{\int \tan^2(x)\sec^2(x)~dx-\int \tan^2(x)~dx}\\
 
&&\\
 
& = & \displaystyle{\int \tan^2(x)\sec^2(x)~dx-\int (\sec^2x-1)~dx.}\\
 
\end{array}</math>
 
|-
 
|using the identity again on the last equality.
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|So, we have
 
|-
 
|
 
::<math style="vertical-align: -13px">\int \tan^4(x)~dx=\int \tan^2(x)\sec^2(x)~dx-\int (\sec^2x-1)~dx.</math>
 
|-
 
|For the first integral, we need to use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -5px">u=\tan(x).</math> Then, <math style="vertical-align: -5px">du=\sec^2(x)dx.</math>
 
|-
 
|So, we have
 
|-
 
|
 
::<math style="vertical-align: -13px">\int \tan^4(x)~dx=\int u^2~du-\int (\sec^2(x)-1)~dx.</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 3: &nbsp;
 
|-
 
|We integrate to get
 
|-
 
|
 
::<math>\begin{array}{rcl}
 
\displaystyle{\int \tan^4(x)~dx} & = & \displaystyle{\frac{u^3}{3}-(\tan(x)-x)+C}\\
 
&&\\
 
& = & \displaystyle{\frac{\tan^3(x)}{3}-\tan(x)+x+C.}\\
 
\end{array}</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;
 
|-
 
| &nbsp;&nbsp; <math>\frac{\tan^3(x)}{3}-\tan(x)+x+C</math>
 
|}
 
 
[[009B_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]
 
[[009B_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 17:12, 12 November 2017

Evaluate the integral:


Solution


Detailed Solution


Return to Sample Exam